Antibacterial Effects of Turmeric Extract on Oral Streptococcus Infections and Gingivitis - Alaa Yaqoob Rahi; Ali Abather Abdal Wahid (American Journal of Biology and Natural Sciences, 2025)
This study investigates the antibacterial and anti-inflammatory effects of turmeric extract on oral Streptococcus infections and gingivitis, highlighting its potential as a natural therapeutic agent for oral health. The findings demonstrate that turmeric extract, rich in curcumin, exhibits significant antibacterial activity against key pathogens such as Streptococcus mutans and Streptococcus sobrinus , which are primary contributors to dental caries. Using the disk diffusion method, turmeric extract showed dose-dependent growth inhibition, with zones of inhibition increasing from 12 mm at 100 µg/mL to 25 mm at 300 µg/mL . The Minimum Inhibitory Concentration (MIC) was determined to be 200 µg/mL for S. mutans and 250 µg/mL for S. sobrinus, indicating its potency even at relatively low concentrations. In addition to its antibacterial properties, turmeric extract significantly reduced inflammatory markers associated with gingivitis. Level of interleukin-6 (IL-6) and necrosis of tumor necrosis factor-alpha (TNF-α) decreased by 55.5% and 60% respectively. After two weeks of treatment. These results underscore curcumin’s ability to modulate inflammatory pathways by inhibiting NF-κB and neutralizing reactive oxygen species (ROS) as supported by existing literature. The profile of turmeric extract also favorable with only mild dry mouth reported in 6.6% of participants while the majority experienced no side effects. Clinically, 66.7% of patients showed significant improvement in gingival health and 26.7% demonstrated moderate improvement reflecting its efficacy in managing gingivitis. Also the study provides robust evidence for the dual antibacterial and anti-inflammatory properties of turmeric extract, making it a promising natural alternative for preventing and treating oral infections and gum disease. Its safety, tolerability and ease of incorporation into daily oral care routines further enhance its practical utility. Future research should focus on optimizing formulations exploring synergistic combinations and conducting large scale clinical trials to validate these findings and expand its applications in preventive dentistry